2012
DOI: 10.1038/srep00961
|View full text |Cite|
|
Sign up to set email alerts
|

Centenarians, but not octogenarians, up-regulate the expression of microRNAs

Abstract: Centenarians exhibit extreme longevity and a remarkable compression of morbidity. They have a unique capacity to maintain homeostatic mechanisms. Since small non-coding RNAs (including microRNAs) are implicated in the regulation of gene expression, we hypothesised that longevity of centenarians may reflect alterations in small non-coding RNA expression. We report the first comparison of microRNAs expression profiles in mononuclear cells from centenarians, octogenarians and young individuals resident near Valen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
58
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 24 publications
13
58
1
1
Order By: Relevance
“…Nine miRNAs had correlations with p values<0.05 (Table 3). Four of these miRNAs (miR-374, 376, 29, 378) have been shown in prior studies to be differentially expressed between older and younger persons in separate profiling experiments [18, 20, 21]. miR-374 was also downregulated in older participants in an earlier study [18], but in contrast with our study, miR-376 was upregulated in older participants in another report [20].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Nine miRNAs had correlations with p values<0.05 (Table 3). Four of these miRNAs (miR-374, 376, 29, 378) have been shown in prior studies to be differentially expressed between older and younger persons in separate profiling experiments [18, 20, 21]. miR-374 was also downregulated in older participants in an earlier study [18], but in contrast with our study, miR-376 was upregulated in older participants in another report [20].…”
Section: Discussioncontrasting
confidence: 83%
“…Because miRNAs and aging genetic pathways are conserved from nematodes to humans, an increasing number of human miRNA studies have been carried out over the past several years. These studies have shown differential abundance of multiple miRNAs in peripheral blood mononuclear cells (PBMCs) or serum/plasma when comparing younger and older adults [1621]. Sredni et al found that changes in global miRNA levels, but not in mRNA levels, are associated with healthy aging in young adult women [16].…”
Section: Introductionmentioning
confidence: 99%
“…mRNA and miRNA expression profiles of different human tissues during aging reveal the existence of a common pattern of defined transcriptional and epigenetic changes as well as tissue-specific age-related alterations (ElSharawy et al, 2012; Li et al, 2009; Maes et al, 2009; Ren et al, 2012; Santarosa et al, 2009; Serna et al, 2012). …”
Section: Hallmarks Of Cellular Senescencementioning
confidence: 99%
“…One such study found a signifi cant overlap of miRNA profi les in circulating mononuclear cells between centenarians and young individuals but not with octogenarians, by principle component analysis (Serna et al 2012 ). The small ncRNA included 7 species up-regulated in centenarians compared to young individuals and 102 as compared to octogenarians.…”
Section: Mirna Aging and Longevitymentioning
confidence: 98%